2011
DOI: 10.1016/j.ejvs.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-term Outcome after Thoracic Endovascular Aortic Repair (TEVAR) for Acute Complicated Type B Aortic Dissection

Abstract: In patients with acute complicated type B aortic dissection, TEVAR can be performed with excellent early and long-term survival, whereas morbidity and long-term durability must be further elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 22 publications
(25 reference statements)
6
65
2
Order By: Relevance
“…Because of the high morbidity and mortality associated with surgery of the descending aorta, medical treatment is generally advocated for uncomplicated cases. However, about 30%-42% of acute Type B dissections at clinical presentation are complicated by hemodynamic instability or rupture, aortic expansion (greater than 5 cm), retrograde dissection into the ascending aorta, and malperfusion (visceral and/or peripheral), all of which can result in high risk of spontaneous death and are indications for surgical repair (Estrera et al, 2006;Fatorri et al, 2008;Green & Kron, 2003;Luebke & Brunkwall, 2010;Steuer et al, 2011). The ideal operation for acute Type B dissection is replacement of as little of the descending thoracic aorta as is necessary.…”
Section: Type B Interventionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of the high morbidity and mortality associated with surgery of the descending aorta, medical treatment is generally advocated for uncomplicated cases. However, about 30%-42% of acute Type B dissections at clinical presentation are complicated by hemodynamic instability or rupture, aortic expansion (greater than 5 cm), retrograde dissection into the ascending aorta, and malperfusion (visceral and/or peripheral), all of which can result in high risk of spontaneous death and are indications for surgical repair (Estrera et al, 2006;Fatorri et al, 2008;Green & Kron, 2003;Luebke & Brunkwall, 2010;Steuer et al, 2011). The ideal operation for acute Type B dissection is replacement of as little of the descending thoracic aorta as is necessary.…”
Section: Type B Interventionsmentioning
confidence: 98%
“…Its extension can proceed distally into arteries branching off the aorta. International registry data demonstrate that roughly one in three dissections is of Type B (Steuer et al, 2011). Figure 2A shows a three-dimensional reconstruction from a contrast-enhanced computed tomographic (CT) angiogram of a 45-year-old woman with Stanford Type A AD; however, there is no external visual abnormality of this patient's aorta (see Supplemental Digital Content Video 2: Three-dimensional Type A AD, available at http://links.lww.com/ AENJ/A9).…”
Section: Aortic Dissection Classification Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relative infancy of thoracic endovascular aortic repair (TEVAR) [13] and the shortage of prospective randomized trials, there is a growing and converging evidence in literature that suggests a substantial early mortality advantage of TEVAR over open surgery and that supports its routine employment in patients with complicated acute type B dissection (Table1) [14][15][16][17][18][19][20]21 ].…”
Section: Aims and Rationalementioning
confidence: 99%
“…5,6 Open surgery for aneurysmal degeneration of chronic dissections of the DTA has been associated with considerable morbidity and mortality. 7,8 In light of the improved outcomes with endovascular therapy of complicated, acute aortic dissections, 9,10 several single institutions have investigated the use of thoracic endovascular aneurysm repair (TEVAR) in the setting of chronic type B dissections; these studies have reported favorable, intermediate outcomes. 5,11 However, several questions remain regarding the application of TEVAR to aneurysmal degeneration of chronic DTA dissections.…”
mentioning
confidence: 99%